Optimal site selection of electric vehicle charging stations exploiting multi-criteria decision analysis: The case of Greek municipalities - Sarmas, Elissaios; Skaloumpakas, Panagiotis; Kafetzis, Nikolaos; Spiliotis, Evangelos; Lekidis, Alexios; Marinakis, Vangelis; Doukas, Haris (Technical Annals, 2023)
The opportunities created in the Greek electric vehicle (EV) market have allowed potential investors to participate in the development of the EV charging infrastructure of the country. Yet, the decision process of relevant stakeholders for strategic investments is challenging, involving the identification of the most promising charging sites from a set of multiple alternative locations of various features that may significantly affect their business competitive advantage. This paper attempts to facilitate decision making in such settings using a comprehensive, yet thorough multi-criteria decision analysis framework. The proposed approach is validated considering ten Greek municipalities of different characteristics. The results show- case the overall strengths of the proposed approach and its utility in the strategic planning process of potential investors.